Design of polymeric stabilizers for size-controlled synthesis of monodisperse gold nanoparticles in water - Wang, Zhenxin (Langmuir : the ACS journal of surfaces and colloids, 2007)
A new methodology is described for the one-step aqueous preparation of highly monodisperse gold nanoparticles with diameters below 5 nm using thioether- and thiol-functionalized polymer ligands. The particle size and size distribution was controlled by subtle variation of the polymer structure. It was shown that poly(acrylic acid) (PAA) and poly(methacrylic acid) (PMAA) were the most effective stabilizing polymers in the group studied and that relatively low molar mass ligands (approximately 2500 g/mol) gave rise to the narrowest particle size distributions. Particle uniformity and colloidal stability to changes in ionic strength and pH were strongly affected by the hydrophobicity of the ligand end group. "Multidentate" thiol-terminated ligands were produced by employing dithiols and tetrathiols as chain-transfer agents, and these ligands gave rise to particles with unprecedented control over particle size and enhanced colloidal stability. It was found throughout that dynamic light scattering (DLS) is a very useful corroboratory technique for characterization of these gold nanoparticles in addition to optical spectroscopy and TEM